Way to Cultivating Right Livelihood as a Path Toward Honoring Living - Dat, Nguyen Quoc; Techapalokul, Soontaraporn (Journal of International Buddhist Studies, 2022)
Right livelihood is an integral part of the Buddhist education and practice for everybody in society. Any society that strives for peaceful cohabitation, the right livelihood will be a leading dhamma to happiness, peace and prosperity. This article has two objectives: (1) To study the general view of honoring living and (2) To suggest ways to cultivate right livelihood as a path toward honoring living. The methodology of this research is qualitative approach consisting of two parts — a documentary and an in-depth interview research approaches. The documentary research approach is divided into three stages: 1) Collecting data from five Nikāya, Commentaries (Aṭṭhakathā), research, theses, books, and journals, 2) Data analyzing and systematizing to construct the outline of the study, and 3) Identifying significant results and formulating conclusion and areas for further research. The in-depth interviews research approach involves data collection from the interview with six key informants. The finding shows that SMSDE (Sīla, Mutual respect, Samādhi, Dāna, Ethical act) is suggested as a path for cultivating right livelihood toward honoring living, which is derived from the analysis and synthesis of general view, the Buddhist concept and the Key-informants’ notions of right livelihood. To get the SMSDE as the suggested path toward Honoring Living for monks and laypeople, and all those who seek peaceful cohabitation.